2013
DOI: 10.1063/1.4845535
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of a newly designed 6 degrees of freedom scanning laser head: Application to three-dimensional beam structure

Abstract: A new scanning laser head is designed to use single Laser Doppler Vibrometer (LDV) for performing measurements up to 6 degrees of freedom (DOF) at a target. The scanning head is supported by a rotating hollow shaft, which allows the laser beam to travel up to the scanning head from an opposite direction where an LDV is set up. The scanning head is made of a set of two mirrors, which deflects the laser beam with an angle so that the rotation of the scanning head produces a conical scan. When measurements are pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Recently, automated solutions were developed in order to overcome these limitations. Using a set of mirrors assembled on a rotary hollow shaft, it has been shown that it is possible to measure the three translations and local rotations (6 DOFs) of a point by implementing continuous scanning along circular paths [14,15]. Perhaps the most complete solution can be found in [16], where three SLDVs are assembled on the head of an industrial robot arm.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, automated solutions were developed in order to overcome these limitations. Using a set of mirrors assembled on a rotary hollow shaft, it has been shown that it is possible to measure the three translations and local rotations (6 DOFs) of a point by implementing continuous scanning along circular paths [14,15]. Perhaps the most complete solution can be found in [16], where three SLDVs are assembled on the head of an industrial robot arm.…”
Section: Introductionmentioning
confidence: 99%